Impact of lockdown on emergency general surgery during first 2020 COVID-19 outbreak - Kurihara, Hayato (Eur J Trauma Emerg Surg, 2021)
PURPOSE: To evaluate and analyze the impact of lockdown strategy due to coronavirus disease 2019 (COVID-19) on emergency general surgery (EGS) in the Milan area at the beginning of pandemic outbreak. METHODS: A survey was distributed to 14 different hospitals of the Milan area to analyze the variation of EGS procedures. Each hospital reported the number of EGS procedures in the same time frame comparing 2019 and 2020. The survey revealed that the number of patients during the COVID-19 pandemic outbreak in 2020 was reduced by 19% when compared with 2019. The decrease was statistically significant only for abdominal wall surgery. Interestingly, in 2020, there was an increase of three procedures: surgical intervention for acute mesenteric ischemia (p = 0.002), drainage of perianal abscesses (p = 0.000285), and cholecystostomy for acute cholecystitis (p = 0.08). CONCLUSIONS: During the first COVID-19 pandemic wave in the metropolitan area of Milan, the number of patients operated for emergency diseases decreased by around 19%. We believe that this decrease is related either to the fear of the population to ask for emergency department (ED) consultation and to a shift towards a more non-operative management in the surgeons ‘decision making’ process. The increase of acute mesenteric ischaemia and perianal abscess might be related to the modification of dietary habits and reduction of physical activity related to the lockdown.